3D numerical simulation of shell and multipass tube heat exchanger - Belacel, Mohsen Abd-Essabour; Benlarbi, Mohamed Ammar; Hachani, Lakhdar (Université Amar Telidji- Laghouat FACULTE : TECHNOLOGIE Département de génie mécanique, 2023)
This work is mainly based on a full 3D predictive numerical simulation in a stationary regime using Ansys/Fluent CFD software to investigate the heat transfer performances of shell and multipass tube heat exchangers. The focus was on a comparative study between four different cases by changing the heat transfer fluids (oil and water) and their arrangement in terms of flow direction at the inlet and outlet (i.e., same or opposite directions). To accomplish this, we’ve examined the temperature distribution and fluid flow patterns within the heat exchanger and assessed its efficiency by estimating the heat transfer rate and energy consumption. Finally, we’ve discussed the ideal configuration in terms of thermal efficiency.
Option : (Énergétique)